2016
DOI: 10.1016/j.jdiacomp.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity is inversely associated with hippocampal volume in African Americans and European Americans with diabetes

Abstract: Aims To assess associations between body mass index (BMI), waist circumference (WC), and computed tomography-determined volumes of pericardial, visceral, and subcutaneous adipose tissue with magnetic resonance imaging-(MRI) based cerebral structure and cognitive performance in individuals with type 2 diabetes (T2D). Methods This study was performed in 348 African Americans (AAs) and 256 European Americans (EAs) with T2D. Associations between adiposity measures with cerebral volumes of white matter (WMV), gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…Similar to our findings, other cohorts with similar prevalence rates of obesity and other vascular risk factors also reported no association between VAT and cognitive function (26,27). In contrast, studies that showed inverse associations between VAT and cognitive performance included participants with lower BMI and lower rates vascular risk factors (28,29).…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our findings, other cohorts with similar prevalence rates of obesity and other vascular risk factors also reported no association between VAT and cognitive function (26,27). In contrast, studies that showed inverse associations between VAT and cognitive performance included participants with lower BMI and lower rates vascular risk factors (28,29).…”
Section: Discussionsupporting
confidence: 88%
“…We did not find evidence of associations with hippocampal volume, which is in contrast to some studies [8,[43][44][45][46], but consistent with others [47,48]. Similarly to cortical thickness, the differences in findings across studies may be due to the timing of adiposity measurement.…”
Section: Discussionsupporting
confidence: 80%
“…A recent study revealed that in non-diabetic AD patients, peripheral insulin resistance was independently associated with reduced hippocampal glucose metabolism and with lower grey matter volume, confirming the hypothesis of insulin resistance impact on AD pathology [ 56 ]. Moreover, neuroimaging studies of the brain reported significant correlations between the presence of T2DM, obesity, and/or peripheral insulin resistance with decreased hippocampal volume [ 67 , 68 ]. Nevertheless, AD is a brain form of diabetes in which both ligand (insulin and IGF-1) deficiencies and receptor resistances coexist and mediate functional impairments in signaling pathways, and this pathology is named type 3 diabetes [ 69 ].…”
Section: Insulin Resistance As a Common Factor Linking Obesity T2dm And Admentioning
confidence: 99%